Examining Self-Compassion's Mediating Effects Between Fear of Failure and Academic Self-Handicapping Among University Students - Fakhri, Nurfitriany; Muhajirah, Khalida; Lukman, Lukman; Buchori, Sahril (Utan Kayu Publishing, 2025)
Academic self-handicapping behaviors exhibit complex relationships with psychological constructs, particularly fear of failure and self-compassion. This investigation examined the differential effects of fear of failure (X₁) and self-compassion (X₂) on self-handicapping tendencies (Y) among university students. The study comprised 398 participants (n=398; 104 males, 294 females) enrolled across five state universities in Makassar, recruited through accidental sampling methodology. Assessment instruments included the Performance Failure Appraisal Inventory Long-Form (modified), the Self-Handicapping Scale (modified), and the Indonesian adaptation of the Self-Compassion Scale. Utilizing ordinal regression analysis, the results revealed a significant positive association between fear of failure and self-handicapping (b = 0.058, p less than 0.001), while self-compassion demonstrated a significant negative relationship (b = -0.045, p less than 0.001). The combined predictive model accounted for 22.4% of the variance in self-handicapping behaviors (Nagelkerke R² = 0.224). These findings contribute to the theoretical understanding of self-handicapping mechanisms and hold practical implications for developing targeted interventions within university student support services. The results may inform the design and implementation of evidence-based training programs addressing maladaptive academic behaviors among university students.